A review of studies related to Arabic language learning based on the Common European Framework of Reference for Language (CEFR) - Abdullah, Mohammad Roshimi; Yaakob, Mohd Aizul; Zulkifli, Muhammad Firdhaus; Sahrir, Muhammad Sabri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2023)
In 2001, the European Union (CoE) introduced the Common European Framework of Reference for Language (CEFR) to measure the competency and mastery of languages found in Europe and other languages in the world. In the context of Arabic language education, Saudi Arabia was one of the first countries to implement Arabic language proficiency measurements based on CEFR standards, particularly at Umm al-Qura University, Mecca, and Saudi Electronic University. That, this article aims to gather studies related to Arabic language proficiency based on the CEFR standard. In addition, this article also provides added value by analyzing each study to provide an explicit overview of the studies. In order to achieve the goal, qualitative methods are used, where library methods and document analysis are practiced. CEFR-related studies and articles will be collected and analyzed using inductive and deductive methods. The analysis of these findings has also found that five main themes have been debated, namely the need to establish a proficiency standard in Arabic, a general explanation regarding the proficiency of Arabic language standards based on CEFR, the implementation of Arabic language proficiency based on CEFR standards in Higher Education Institutions, indicators of Arabic language proficiency based on standards CEFR and alignment of Arabic teaching materials based on CEFR standards.